Elderly nutritional status effection salivary anticandidal capacity against Candida albicans - Ria Puspitawati; Nurtami Soedarsono; Elisabeth A Putri; Anissha D Putri; Boy M Bachtiar (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: Elderly often suffer malnutrition and oral candidiasis. Candida albicans (C. albicans) which is the most prominent cause of oral candidiasis, is one of commensal oral micro-flora. Nutritional status affect the characteristic of saliva. Saliva is the regulator in the development of C. albicans from comensal into pathogen. Purpose: The purpose of this study was to determining the correlation between elderly nutritional status with salivary total protein and its activity in inhibiting C. albicans growth and biofilm formation. Methods: Using mini nutritional assessment 30 elderly were classified into normal and malnutrition groups. Total protein of unstimulated saliva was measured using Bradford protein assay. The colony forming unit (CFU) of C. albicans was counted on 72 hours on SDA cultures without (control) or with 2 hour saliva exposure. Biofilm formation was analyzed from the optical density of 10–5 C. albicans suspension without saliva exposure (control) or with exposure of 10.000 μg/ml saliva and incubated in 37° C for 2 days. The suspension was put into 96 well plates, stained with crystal-violet dye, and analyzed using microplate reader. Differences between groups were analyzed using independent t-test or Kruskall-Wallis. Correlation between variables was analyzed using Spearman test. Results: Salivary total protein of normal elderly (1.113.5 ± 1.1143.3) was higher than those of malnutrition (613.6 ± 253.6) but not statistically significant (p > 0.05). The CFU of C. albicans exposed to saliva of normal samples (2.060 cfu/ml) was significantly lower than control (24.100 cfu/ml) and those exposed to malnutrition saliva (5.513.3 cfu/ml). C. albicans biofilm formation is highest in controls (0.177), lower in those exposed to malnourished saliva (0.151) and lowest in those exposed to saliva of good nourished elderly (0.133). Conclusion: Although does not cause significant decrease of salivary total protein, malnutrition in elderly results in lower capacity of saliva in inhibiting the growth and declining the virulence of C. albicans.Latar belakang: Lansia sering menderita malnutrisi dan kandidiasis oral. Candida albicans yang merupakan penyebab utama terjadinya candidiasis, adalah salah satu mikroflora rongga mulut yang bersifat konvensional. Malnutrisi memengaruhi karakteristik saliva. Saliva merupakan regulator utama perkembangan Candida albicans (C. albicans) dari sifat konvensional menjadi bersifat patogen.Tujuan: Tujuan dari penelitian ini adalah untuk menentukan korelasi antara status gizi lansia dengan total protein dan aktivitas saliva dalam menghambat pertumbuhan dan pembentukan biofilm C. albicans. Metode: Menggunakan mini nutritional assessment, 30 lansia diklasifikasikan menjadi kelompok gizi baik dan gizi buruk. Total protein unstimulated saliva diukur dengan metode Bradford protein assay. Colony forming unit (CFU) dihitung pada kultur C. albicans pada saburaud dextrose agar (SDA) berusia 72 jam yang sebelumnya telah dipaparkan saliva selama 2 jam. Kontrol adalah kultur C. albicans tanpa paparan saliva. Pembentukan biofilm adalah pengukuran optical density suspensi 10–5 C. albicans tanpa paparan saliva (kontrol) atau dengan paparan saliva 10.000 μg/ml dan diinkubasi pada suhu 37° C selama 2 hari. Suspensi tersebut kemudian dimasukkan ke dalam 96 well plates, diberi pewarna crystal violet, dan diukur menggunakan microplate reader. Analisis data menggunakan uji beda t Independen atau Kruskall-Wallis, dan uji korelasi Spearman. Hasil: Total protein saliva lansia gizi baik (1.113,5 ± 1.1143,3) lebih tinggi dari lansia gizi buruk (613,6 ± 253,6) tetapi tidak bermakna secara statistik (p > 0,05). Pembentukan koloni C. albicans yang terpapar saliva lansia gizi baik (2.060 cfu/ml) secara signifikan lebih rendah dari kontrol (24.100 cfu/ml) dan daripada yang terpapar saliva lansia gizi buruk (5.513,3 cfu/ml). Pembentukan biofilm C. albicans tetinggi pada kontrol (0,177), lebih rendah pada yang terpapar saliva gizi buruk (0,151) dan terrendah pada yang terpapar saliva gizi baik (0,133). Kesimpulan: Meskipun malnutrisi tidak menyebabkan penurunan total protein saliva lansia, tetapi menurunkan kapasitasnya dalam menghambat pertumbuhan dan mengurangi virulensi C. albicans.